Experimental and Numerical Analysis Study on Loess-Lime Structures Used for Lateral Antiseepage in Deep Collapsible Ground Embankment - Zhengrui Zhang; Siti Jahara Matlan; Lili Zhang; Hao Wang (Advances in Civil Engineering)
The focus of this study was to investigate the effect of loess soil treated with lime on the lateral-seepage response. Three groups of box experiments were carried out to study the lateral-seepage effect under different types of loess-lime structures. Automated testing systems were designed to perform experiments and collect data. Additionally, numerical analysis of lateral-seepage impact and embankment settlement was performed. Finally, moisture content and settlement were monitored to quantify lateral-seepage effect results under corresponding loess-lime treatment. Results showed that loess-lime compaction piles and diaphragm wall structures could effectively prevent lateral seepage, and the latter was better. The simulated results are similar to the measured values of the box experiment, which indicates the accuracy of the simulation analysis and further supports the experimental results of this study.